Internet addiction and its cognitive behavioral therapy - (:unkn) unknown (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2010)
Despite its short history, intemet has become an indispensible part of daily life. It has been observed that individuals who increasingly spend most of their time in the virtual world, lose control of their habit and experience dysfunctionalities in their professional, social and private lives. Today this fact emerges as a widely discussed topic. Prevalance of intemet addiction is reported to be around 1.5-8.2%. Prevalence discrepancies may be explained by different scales used to diagnose 'intemet addiction', different methods employed for different studies, differences among target populations for each study and social and cultural differences. Cognitive behavioural interventions (CBI) are the most efficient and widely used treatment approach for intemet addiction. This paper reviews how intemet addiction is conceptualized and treated by cognitive behavioural approaches. As intemet addiction have lots of similarities to alcohol and drug addiction, similar CBI are used in treatment of both conditions. Since it is impossible to eliminate use of intemet from daily life, methods that aim to control the amount of time spent and purpose of intemet use become the most prominent elements of treatment interventions. There is still room for controlled and standardised studies to facilitate further understanding of 'Intemet Addiction', that will eventually lead to better and more comprehensive treatments. (Anatolian Journal of Psychiatry 2010; 11:261-268)
Keywords: Internet; intemet addiction; cognitive behavioral therapy; pathological intemet use; DISORDER; METACOGNITIONS; QUESTIONNAIRE; SHYNESS